KECEMASAN KEPEMIMPINAN KEPALA SEKOLAH BARU DALAM ADAPTASI JABATAN DAN MANAJEMEN KONFLIK - Ardiansyah; Ermawati, Erlin; Sudadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
New school principals face significant psychological challenges during their leadership transition, particularly in the form of leadership anxiety that affects the quality of role adaptation and conflict management. Method: This study employed a library research approach with content analysis technique, systematically reviewing ten scientific literature sources published between 2021 and 2025, selected from credible academic databases. Results: Findings reveal that leadership anxiety among new principals stems from accumulated role pressure, excessive job burdens, and the gap between idealized expectations and actual field realities. Conflict management capacity is simultaneously influenced by psychological and organizational factors, where adaptive school culture and transformational leadership style serve as key protective factors. A reciprocal relationship exists between leadership anxiety and conflict management effectiveness, forming a cycle that requires deliberate intervention through appropriate leadership strategies. Discussion: Adaptive and transformational leadership approaches are proven effective in reducing anxiety while simultaneously enhancing conflict management capacity, making structured induction and mentoring programs an urgent necessity within Indonesia's educational leadership development system.